Learning English Listening Using Social Media - Pramesti, Hanung Salsabila; Sripraset, Chattaphorn; Larasati, Oktavia Dwi Putri (Applied Research on English Education (AREE), 2024)
This study aims to examine ELT learners who acquire English language skills by listening to content on social media platforms. The instruments used in this research consisted of a questionnaire that assesses learners’ interest in learning through social media platforms. The questionnaire consists of 30 items that responders are required to complete. The participants were the 60 bachelors degree of English Education Department. The findings reveal multiple variables that impact individuals' auditory comprehension abilities. The first issue is challenging pronunciation, obscure terminology, diverse accents, and unengaging content, and the final concern revolves around insufficient practice by individuals. In order to comprehend the current English-language technologies available today, acquiring the skill of active listening can be achieved through multiple methods.